Search for a W ' or Techni-rho Decaying into WZ in pp Collisions at root s=7 TeV - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Aguilo, E.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Messineoa, A.; et al. (Amer Physical Soc, 2012)
A search is performed in pp collisions at root s 7 TeV for exotic particles decaying via WZ to final states with electrons and muons. The data sample corresponds to an integrated luminosity of approximately 5 fb(-1). No significant excess is observed in the data above the expected standard model background. Upper bounds at 95% confidence level are set on the production cross section of the W' boson described by the sequential standard model and on the W' WZ coupling. W' bosons with masses below 1143 GeV are excluded. Limits are also set in the context of low-scale technicolor models, under a range of assumptions concerning the model parameters.